INOVASI PELAYANAN PUBLIK MELALUI APLIKASI “E-DUKCAPIL” PEMBUATAN KARTU KELUARGA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARAWANG - Neni Suwarni; Kariena Febriantin; Cucu Sugiarti; Evi Priyanti (Journal Publicuho, 2021)
This study aims to analyze public service innovations through the application "E-dukcapil" in making family cards at the Department of Population and Civil Registration, Karawang Regency. The research conducted is qualitative research, in this research is descriptive in nature, namely to describe the reality of the events under study. The focus of this research is using the innovation attribute theory by Rogers, namely: (1) relative advantage, (2) suitability, (3) complexity, (4) possibility of experimentation, (5) ease of observation. Through observation data collection techniques, in-depth interviews and documentation. With the number of informants as many as 3 people. The results showed that the innovation of family card services through the "E-dukcapil" application was not entirely ideal. This is because the application has only been implemented for 3 months, and problems such as server disruptions are still common. Lack of public understanding of the use of information technology and the lack of human resources of the implementing apparatus, namely the number of Civil Servants (PNS) in the Department of Population and Civil Registration of Karawang Regency, which is only equivalent to 40 people.